Identification of Occupational Health And Safety Potential Hazards In The Production Process at UD. Evan Nias Regency - Desniat Zandroto; Serniati Zebua (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Occupational Health and Safety (OHS) is a fundamental aspect in improving employee performance and company productivity. This research aims to identify OHS potential hazards, analyze the implementation of OHS procedures, and evaluate control efforts in minimizing OHS potential hazards at UD. Evan, Nias Regency. The research uses a qualitative approach with descriptive methods where data is obtained through in-depth interviews with informants and supported by direct observation and documentation studies. The research results show that the identified potential hazards include physical hazards (being struck by heavy objects, being hit by machines, slippery floors), chemical hazards from production materials, ergonomic hazards (incorrect body posture, repetitive movements), and work accident risks. Implementation of OHS procedures is carried out through strict OHS policies, provision of complete Personal Protective Equipment (PPE), periodic training, as well as routine supervision and audits. Control efforts include machine and equipment modifications, periodic risk evaluations, strict report follow-up procedures, and effective feedback mechanisms. Although OHS implementation is already quite good, there are still obstacles such as lack of employee awareness, budget limitations, and resistance to changes in work procedures. Stronger commitment from management is required in improving continuous training programs, safety technology investment, and building a mature safety culture so that OHS implementation is optimal and sustainable.